A COMPARATIVE STUDY OF SUPERNATURAL EVENTSBETWEEN “KIMI NO NAWA” AND “TENKI NO KO” - Humairah, Andi Ananda; Abdullah, Abdullah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
The aim of this research is to find out the supernatural events occurring in “Kimi no Nawa” and“Tenkino Ko” Films using the Dunwich (2002) Supernatural theory and Comparative Literatureapproach based on elements of film. This research used descriptive qualitative research in order todescribe the phenomenon and its characteristics that are related to the topic. Using Dunwich'stheory, the researchers categorized the supernatural events in both films based on 5 out of 10aspects. The researchers also compared the supernatural events with the elements of film in orderto classify the supernatural events inboth films to find the differences and similarities. The resultof this study indicates that there are 9 similarities and 10 differences found in two films based onPlot, Structure, Visual, Conflict, and Resolution elements of film. 12 supernatural eventsarecaptured in Kimi no Nawa and 25 supernatural events are captured in Tenki no Ko based onPlantasms and Ectoplasms, True tales of Ghosts and Hauntings, Spiritualism, Ghostly superstitions,and Deities of Death and the Underworld supernatural aspects. There are no connections found inthis research between the supernatural events and reality. As a conclusion for this research, theresearchers were able to classify the supernatural events and compare them.